Analisis Pasang Surut Sungai Kapuas Kota Pontianak Menggunakan Metode Admiralty - Santoso, Hendi; Saputra, Robin; Munandar, Rizqan Khairan; Zibar, Zan; Dodi, Dodi (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2024)
This study analyzes the tidal patterns in the Kapuas River, Pontianak, using the Admiralty Method to determine the type and characteristics of tides and their implications for flood management and navigation along the river channel. Based on harmonic analysis, the tides in the Kapuas River are classified as mixed, with a dominant semidiurnal component, resulting in two high and two low tides per day with varying heights. This tidal type potentially increases flood risk, particularly when peak tides coincide with high upstream discharge. This condition heightens the risk of river overflow, necessitating mitigation measures such as tidal monitoring and effective drainage planning. Additionally, tidal fluctuations impact the depth of the river channel, critical for navigation activities. At high tide, water depth increases, facilitating large vessel navigation, while at low tide, some channels may become shallow, hindering navigation. This study’s findings highlight the importance of integrating tidal predictions in coastal area management and river channel regulation in Pontianak to reduce flood risk and support safe navigation.